Cryopreservation-induced proteomic alterations in Pêga donkey (Equus asinus) spermatozoa - Camilo Jose Ramirez-Lopez; Isabella Cristina Tolêdo Alves Costa; Wassali Valadares de Sousa; Yara Martins da Silva; Faider Alberto Castano Villadiego; Tayna Bolsam da Silva; Renner Philipe Rodrigues Carvalho; Arabela Guedes de Azevedo Viana; Jose Carlos Montes-Vergara; Mariana Machado-Neves; Simone Eliza Facioni Guimaraes; Fabio Cesar Sousa Nogueira; et al. (Cryobiology, 2026)

Dietary modulation of antimicrobial peptides ( HAMP and LEAP2 ) in Chinook salmon ( O ncorhynchus tshawytscha ) fed a phytobiotic functional diet: Integrated genomic characterisation and tissue‐specific expression - Roberta Marcoli; Jane E. Symonds; Seumas P. Walker; Cesar Lopez; Mark A. Preece; Christopher Battershill; Steve Bird (Journal of Fish Biology, 2026)
Antimicrobial peptides (AMPs) are key components of the innate immune system in fish, providing rapid protection against microbial pathogens. Among these, the liver‐expressed antimicrobial peptides (LEAPs), comprising LEAP‐1 (hepcidin; HAMP) and LEAP‐2, play central roles in host defence and iron regulation. In this study, we present an integrated characterisation of the genomic organisation, tissue expression and dietary responsiveness of HAMP and LEAP2 paralogues in Chinook salmon ( Oncorhynchus tshawytscha ), and assess their modulation by a phytobiotic functional feed under commercial farming conditions. Genome mining identified three functional HAMP and three LEAP2 paralogues in Chinook salmon, all retaining conserved features typical of their respective peptide families and arising from salmonid‐specific genome duplication events. Constitutive expression analysis revealed liver‐dominant expression of HAMP, whereas LEAP2 paralogues exhibited distinct tissue‐specific profiles, with LEAP2.1 and LEAP2.2 expressed predominantly in the liver and skin, and LEAP2.3 largely restricted to gills and skin. A six‐month feeding trial using a functional diet supplemented with the phytobiotic NatControl™ resulted in marked tissue‐ and paralogue‐specific upregulation of AMP gene expression. HAMP expression was upregulated across multiple immune‐relevant tissues, including head kidney, skin, spleen, liver and gills. LEAP2 paralogues also showed clear dietary responsiveness, with LEAP2.1 and LEAP2.2 upregulated in the liver and kidney, and LEAP2.3 showing strong upregulation in gills. Despite these molecular responses, no significant differences in growth or survival were observed between diet groups. Together, these findings provide the first integrated characterisation of HAMP and LEAP2 systems in Chinook salmon, demonstrate their sensitivity to dietary immunomodulation and support their use as molecular biomarkers of functional immune priming. The results further indicate that NatControl™ acts as an effective immunostimulant, enhancing innate immune readiness without compromising growth performance under non‐challenging conditions.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Labile and stable organic carbon in soils of cacao agroforestry systems compared to forest and pasture in the Colombian Amazon - Juan Carlos Suárez; Cesar Julian Lopez; Wilson Rodriguez (Agroforestry Systems, 2026)
The study analyzed labile and stable SOC fractions in different land use systems in the Colombian Amazon. The research included cacao-based Agroforestry Systems (cAFS), full-sun cocoa plantations, forests, and pastures, using a factorial design with land use and soil depth as factors. Land use significantly affected carbon fractions, explaining 51% of variance ( P −1 ) and lowest in Pasture (2.76 g C kg −1 ). For humic acids, full-sun cacao showed the highest values (9.55 g C kg −1 ) followed by Capiron (7.75 g C kg −1 ). Total Humic Extract was maximum in full-sun cacao (27.68 g C kg −1 ) and minimum in Pasture (18.99 g C kg −1 ). The polymerization index was higher in Pasture (1.87) and full-sun cacao (1.46). The degree of humification was highest in full-sun cacao (64.78%), while the humification ratio showed maximum values in full-sun cacao (84.9%) and minimum in Forest (36.86%). These patterns generally persisted at deeper soil layers, demonstrating the potential of cAFS as a sustainable alternative for land use and carbon sequestration.

Why not be larger in wave action sites? Energetic constraints due to body size in hermit crabs - Cesar Rubio-Lopez; Guillermina Alcaraz (Marine Environmental Research, 2025)

Performance of skimmed milk flocculation and real-time polymerase chain reaction for the concentration, detection, and quantification of Taenia solium in urban wastewater from an endemic region of the Peruvian central highlands - Cesar A. Valdivia-Carrera; Ana C. Ho-Palma; Luis A. Gomez-Puerta; Daniel A. Andrade; Brenda L. Gonzales; Maria T. Lopez-Urbina; Armando E. Gonzalez; Javier A. Bustos; Hector H. Garcia; Sarah Gabriël; Seth E. O'Neal; Eloy Gonzales-Gustavson (Science of The Total Environment, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

First evidence that antibiotic-resistant bacteria are inactivated by chemical species produced through the solar photosensitization of ciprofloxacin in water - Martha I. Verbel-Olarte; Efraím A. Serna-Galvis; David M. Jimenez-Lopez; Sindy D. Jojoa-Sierra; Jazmín Porras; Cesar Pulgarin; Ricardo A. Torres-Palma (Science of The Total Environment, 2025)

Characterization of nanoparticles used as precipitant agents for in situ upgrading of heavy crude oils via single particle inductively coupled plasma mass spectrometry (spICP-MS) - Deja Hebert; Yanila Salas-Ortiz; Jenny Nelson; Cesar Ovalles; Francisco Lopez-Linares; Estrella Rogel; Laura Poirier; Phoebe Zito (Fuel, 2025)

The impact of settleable atmospheric particulate on the energy metabolism, biochemical processes, and behavior of a sentinel mangrove crab - Anieli C. Maraschi; Cesar Rubio-Lopez; Solana M. Snitman; Iara C. Souza; Brian Pichardo-Casales; Guillermina Alcaraz; Magdalena V. Monferrán; Daniel A. Wunderlin; Claudia Caamal-Monsreal; Carlos Rosas; Marisa N. Fernandes; Mariana V. Capparelli (Journal of Hazardous Materials, 2024)

An imperative for soil spectroscopic modelling is to think global but fit local with transfer learning - Raphael A. Viscarra Rossel; Zefang Shen; Leonardo Ramirez Lopez; Thorsten Behrens; Zhou Shi; Johanna Wetterlind; Kenneth A. Sudduth; Bo Stenberg; Cesar Guerrero; Asa Gholizadeh; Eyal Ben-Dor; Mervin St Luce; et al. (Earth-Science Reviews, 2024)

Birth weight, growth indices, and seminal parameters in male offspring are resilient features to maternal pre-conceptional dietary manipulation in sheep - Cesar A. Rosales-Nieto; Bradford W. Daigneault; Jennifer N. Roberts; Rodrigo Sánchez-López; Barbara Makela; Yong Pu; Richard Ehrhardt; João H. Jabur Bittar; Almudena Veiga-Lopez (Domestic Animal Endocrinology, 2024)

Use of remote sensing for linkage mapping and genomic prediction for common rust resistance in maize - Alexander Loladze; Francelino A. Rodrigues; Cesar D. Petroli; Carlos Muñoz-Zavala; Sergio Naranjo; Felix San Vicente; Bruno Gerard; Osval A. Montesinos-Lopez; Jose Crossa; Johannes W.R. Martini (Field Crops Research, 2024)

Surveillance of SARS-CoV-2, rotavirus, norovirus genogroup II, and human adenovirus in wastewater as an epidemiological tool to anticipate outbreaks of COVID-19 and acute gastroenteritis in a city without a wastewater treatment plant in the Peruvian Highlands - Cesar A. Valdivia-Carrera; Ana C. Ho-Palma; Astrid Munguia-Mercado; Karoll Gonzalez-Pizarro; Claudia Ibacache-Quiroga; Alejandro Dinamarca; Milan Stehlík; Marta Rusiñol; Rosina Girones; Maria T. Lopez-Urbina; Anani Basaldua Galarza; Eloy Gonzales-Gustavson (Science of The Total Environment, 2023)

Bifurcaria bifurcata extract exerts antioxidant effects on human Caco-2 cells - María-Aránzazu Martínez; Hugo Aedo; Bernardo Lopez-Torres; Jorge-Enrique Maximiliano; María-Rosa Martínez-Larrañaga; Arturo Anadón; Marta Martínez; Cesar Peteiro; Mercedes Cueto; Susana Rubiño; María Hortos; Irma Ares (Environmental Research, 2023)

Fish surveys on the move: Adapting automated fish detection and classification frameworks for videos on a remotely operated vehicle in shallow marine waters - Rod M. Connolly; Kristin I. Jinks; Cesar Herrera; Sebastian Lopez-Marcano (Frontiers in Marine Science, 2022)
Mobile underwater cameras, diver-operated or on underwater vehicles, have become popular for monitoring fisheries. Replacing divers with cameras has clear advantages, such as creating permanent records and accessing waters unavailable to divers. The use of cameras, however, typically produces large quantities of video that are time-consuming to process manually. Automated analysis of underwater videos from stationary cameras using deep learning techniques has advanced considerably in recent years, but the use of mobile cameras potentially raises new challenges for existing methods. We tested how well three automation procedures for stationary underwater cameras, taking an object-centric rather than background-centric approach, performed on surveys of fish using a mobile camera. We analyzed underwear drone videos from reef and seagrass habitat to detect and count two marine fisheries species, luderick ( Girella tricuspidata ) and yellowfin bream ( Acanthopagrus australis ). Three convolutional neural network (CNN) frameworks were compared: Detectron Faster R-CNN, Detectron2 Faster R-CNN (using a Regional Proposal Network, RPN), and YOLOv5 (a single-stage detector, SSD). Models performed well overall. Per frame, overall F1 scores ranged 81.4 - 87.3%, precision 88.2 – 96.0%, and recall 73.2 - 88.2%. For quantifying MaxN per video, overall F1 ranged 85.9 – 91.4%, precision 81.9 – 95.3%, and recall 87.1 – 91.1%. For luderick, F1 was > 80% for all frameworks per frame and 89% or higher for MaxN. For yellowfin bream, F1 scores were lower (35.0 - 73.8% for frames, 43.4 - 73.0% for MaxN). Detectron2 performed poorly, and YOLOv5 and Detectron performed similarly with advantages depending on metrics and species. For these two frameworks, performance was as good as in videos from stationary cameras. Our findings show that object detection technology is very useful for extracting fish data from mobile underwater cameras for the system tested here. There is a need now to test performance over a wider range of environments to produce generalizable models. The key steps required area to test and enhance performance: 1. for suites of species in the same habitats with different water clarity, 2. in other coastal environments, 3. trialing cameras moving at different speeds, and 4. using different frame-rates.

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Chemical, physical, and biological attributes in soils affected by deposition of iron ore tailings from the Fundão Dam failure - Aline Oliveira Silva; Amanda Azarias Guimarães; Bruna Daniela Ortiz Lopez; Carin Sgobi Zanchi; Cesar Florentino Puma Vega; Éder Rodrigues Batista; Fatima Maria de Souza Moreira; Flávia Romam da Costa Souza; Flávio Araújo Pinto; Jessé Valentim dos Santos; Joana Junqueira Carneiro; José Oswaldo Siqueira; et al. (Environmental Monitoring and Assessment, 2021)

Case definitions for skin lesion syndromes in chinook salmon farmed in Marlborough Sounds, New Zealand - Hazel Johnston; Jane Symonds; Seumas Walker; Mark Preece; Cesar Lopez; Barbara Nowak (Journal of Fish Diseases, 2021)
Skin lesions are commonly reported in farmed salmonids. Chinook salmon ( Oncorhynchus tshawytscha ), introduced from California USA, is the only salmonid species commercially farmed in New Zealand, although trout are cultured for release by Fish and Game New Zealand. There are several farming areas in New Zealand, including Marlborough Sounds, Canterbury and Stewart Island. While the industry has not been affected by any of the major production diseases seen internationally, skin lesions have been recorded with an increase in prevalence from 2012 onwards in the Marlborough Sounds and were associated with elevated summer mortalities on farms in 2015. Here we are proposing case definitions for different types of skin lesions for future monitoring and research. Based on our current understanding of the above skin conditions, we developed case definitions for spots, spreading spots, ulcerated spreading spots and Regular Outline Flank Ulcers defining a positive case for three study units, including individual fish, pen/unit and farm.

Local decadal prediction according to statistical/dynamical approaches - Dario Redolat; Robert Monjo; Cesar Paradinas; Javier Pórtoles; Emma Gaitán; Carlos Prado‐Lopez; Jaime Ribalaygua (International Journal of Climatology, 2020)
Dynamical climate models present an initialization problem due to the poor availability of deep oceanic data, which is required for the model assimilation process. In this sense, teleconnection indices, defined from spatial and temporal patterns of climatic variables, are conceived as useful tools to complement them. In this work, the near‐term climate predictability of 35 temperature and 36 precipitation time series of three cities (Barcelona, Bristol and Lisbon) was analysed using two approaches: (a) a statistical–dynamical combination of self‐predictable teleconnection indices and long‐term climate projections on a local scale and (b) dynamical model outputs obtained from drift‐corrected decadal experiments. Fourier and wavelet analyses were used to assess the predictability of seven teleconnection indices thanks to a cross‐validation process (with differentiated training and validation periods). The standardized absolute error of teleconnection‐based prediction was compared with that obtained from a (9) multi‐model ensemble based on the Coupled Model Intercomparison Project Phase 5. Results showed that decadal predictions at horizons between 20 and 30 years are adequate for temperature and precipitation if a teleconnection‐based approach is used, while temperature is better predicted from a 5‐year horizon using drift‐corrected dynamical outputs.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

First detection of spring viraemia of carp virus in common carp ( Cyprinus carpio L.) affected by a septicaemic disease in Mexico - Cesar Ortega; Leticia Cañas‐Lopez; Rute Irgang; Raúl Fajardo; Matías Poblete‐Morales; Benjamin Valladares-Carranza; Diana Tapia‐Cammas; Ruben Avendaño‐Herrera (Journal of Fish Diseases, 2019)
Spring viraemia of carp (SVC) is an infectious disease responsible for severe economic losses for various cyprinid species, particularly common carp ( Cyprinus carpio carpio ). The causative agent is the SVC virus (SVCV), a member of the Sprivivirus genus, Rhabdoviridae family, and a List 1 pathogen notifiable by the World Organization for Animal Health. This study describes the diagnosis of an SVCV pathogen isolated in October 2015 from wild common carp inhabiting a natural lagoon in central Mexico. While neither an epidemic nor fish mortalities were reported, the collected killed specimens exhibited clinical signs of disease (e.g., exopthalmia, moderate abdominal distension and haemorrhaging, as well as internal haemorrhages and adhesions). Histological results of injuries were consistent with the pathology caused by SVCV. This finding was supported by the isolation of a virus in EPC and BF‐2 cells and subsequent RT‐PCR confirmation of SVCV. The phylogenetic analyses of partial SVCV glycoprotein gene sequences classified the isolates into the Ia genogroup. These findings make this the first report of SVCV detection in Mexico, extending the southern geographical range of SVCV within North America. However, since this pathogen was detected in fish inhabiting a natural body of water without tributaries or effluents, it is difficult to estimate the risk of SVCV for other wild/feral cohabitating cyprinid species in the lagoon. The status of this virus is also unknown for other bodies of water within this region.

New advances in the study of the biodiversity of the SCI "Volcanes de fango del golfo de Cádiz" (southwestern Spanish Margin) - Ángel Mateo-Ramírez; Emilio González-García; Carlos Farias; Jose Enrique García Raso; Serge Gofas; Eduardo Lopez Garcia; Pablo J. López-González; Manuel Maldonado; Pablo Marina Ureña; Cesar Megina; Juan Moreira; Lais Ramalho; et al. (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Fleets of robots for environmentally-safe pest control in agriculture - Pablo Gonzalez-de-Santos; Angela Ribeiro; Cesar Fernandez-Quintanilla; Francisca Lopez-Granados; Michael Brandstoetter; Slobodanka Tomic; Stefania Pedrazzi; Andrea Peruzzi; Gonzalo Pajares; George Kaplanis; Manuel Perez-Ruiz; Constantino Valero; et al. (Precision Agriculture, 2017)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Improved sea-urchin embryo bioassay for in situ evaluation of dredged material - M. J. Salamanca; N. Fernández; A. Cesar; R. Antón; P. Lopez; Á. Delvalls (Ecotoxicology, 2009)

An automated sea breeze selection technique based on regional sea‐level pressure difference: WeMOi - Cesar Azorin‐Molina; Joan‐Albert Lopez‐Bustins (International Journal of Climatology, 2008)
A recently defined regional teleconnection pattern for the western Mediterranean basin (western Mediterranean Oscillation, WeMO) has allowed an objective quantification of the synoptic circulation factor on the occurrence of sea breezes. The associated WeMO index (WeMOi) can be used as an initial objective filter for selecting ideal surface pressure conditions for sea breeze development. Applying this filter to the sea breeze database created for Alicante (reference synoptic station) and performing a manual selection method for the 2‐year period (1999–2000), we confirmed the potential use of this objective primary criterion. We used wind speed (WS) and direction (WD) data from 9 coastline meteorological stations to assess the WeMOi applicability to the Iberian Mediterranean coast and the Balearic Isles. The [−1, 1] threshold interval of the daily WeMOi was seen to be a good proxy for detecting weak pressure gradients at surface level. Observational and numerical sea breeze studies require quality databases in order to analyse in depth the main characteristics and physical processes controlling sea breezes. This automated selection technique enabled us to improve the accuracy and processing time of the filter methods for finding sea breeze days by adding a new objective criterion. This new threshold technique [−1, 1], based on regional sea‐level pressure (SLP) difference, is adaptable to any coastal region at mid‐latitudes where a regional barometric dipole can be defined. A regional teleconnection pattern, such as the WeMOi, could be used as a suitable tool for forecasting sea breeze occurrence. Copyright © 2008 Royal Meteorological Society